Strategic Purchasing Plan: Canned Fruit Product Category in Australia and New Zealand - Tania Aveline Tanujaya (iBuss Management, 2017)
To strive as being the leader in the food and beverages industry, multinational companies have been continuously improving its efficiency to optimize its operations and to maximize its profitability. This research focusses on the role of a global procurement co-pack department, which deals with the buying of finished goods from external contract manufacturers. Currently, the sourcing process of Company X’s canned fruit products in Australia and New Zealand is being done ad-hoc. This brings an opportunity to do a research on what is the best sourcing strategy for this product category in order to bring cost savings and operational benefits for the company. This research is conducted in a qualitative method, mainly using the primary and secondary sources from company’s internal archival data, interviews with the global procurement co-pack team, complemented with desk research from the internet. From the research, it shows that company X should leverage competition among suppliers by using the tendering approach. By implementing this strategy, Company X is expected to gain financial benefit for around 10% of the total spending. As for the operational benefits, the company is expected to have less operational issues from suppliers, economies of scale benefits, and less knowledge spillover. Keywords: Purchasing, Procurement Strategy, Contract Manufacturers, Tendering